Volumetric flow and pressure gradient-based leak detection system for oil and gas pipelines. (1st May 2020) - Riaz, Mukarram; Ahmad, Ishtiaq; Khan, Muhammad Nasir; Mond, Muhammad Asim; Mir, Amna
The leakage in oil and gas pipelines results economic losses to petroleum companies and causes damages to the environment. It may occur due to corrosion in the pipe or intentional or unintentional damage by third party intervention. A prompt and accurate leak detection and localisation system is very essential. In this paper, we have developed a nonlinear adaptive model for detection and localisation of leak based on correlation of pressure and volumetric flow at the pipe inlet and outlet. The characteristic changes in the flow mechanics and thermodynamics along a given length of pipeline such as pressure, flow and temperature are adopted in the model. A compensated volume balancing method is proposed for leak detection based on conservation laws of mass, momentum and energy. Leak localisation is based on presence of pressure gradient in the vicinity of the leak. The simulation results show the superior performance of our proposed model. [Received: September 24, 2018; Accepted: March 10, 2019]